Perceptions of healthcare professional about the “PACE Steps to Success” palliative care program for long‐term care: A qualitative study in Switzerland - Pierre‐Alain Charmillot; Lieve Van den Block; Mariska Oosterveld‐Vlug; Sophie Pautex (Nursing Open, 2023)
Abstract Aim This study aimed to examine the healthcare professionals' perceptions after implementing the “PACE Steps to Success” program in the French‐speaking part of Switzerland. Design A qualitative descriptive study. Methods Thematic analysis of semi‐structured face‐to‐face and group interviews with health professionals, PACE coordinators, and managers purposely invited in the four long‐term home facilities that had previously participated in the PACE cluster randomized clinical trial intervention group. Results The PACE program implementation has improved communication with residents regarding end‐of‐life issues and helped identify patients' needs. The introduction of codified tools can complete internal tools and support decision‐making. In addition, the training has promoted inter‐professional collaboration, particularly in the case of care assistants, by defining each profession's specific responsibilities in providing care for older adults.